The effect of major surgery on systemic and splanchnic immune function : examining the two-hit and gut hypotheses of the systemic inflammatory response syndrome - Holland, Jane Catherine (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Surgery, 2006)
The systemic inflammatory response syndrome (SIRS), sepsis and multiple organ dysfunction syndrome (MODS) are recognized sequelae of complex major surgery and underlie significant morbidity and mortality. The systemic immunoinflammation underlying SIRS and MODS in the presence or absence of infection is not fully understood, but two of the current hypotheses are the ‘two-hit’ and gut hypotheses. The ‘two-hit’ hypothesis proposes that if the host immune system has been primed by an initial insult, the immune response to any subsequent or second msult will be greatly amplified. The gut hypothesis incriminates bacteria and endotoxins derived from the gastrointestinal tract as triggers, which initiate, perpetuate or exacerbate a systemic inflammatory response resulting in the development of SIRS. In this work, a cohort of patients undergoing curative surgery for upper gastrointestinal malignancy was studied, some of who received neoadjuvant chemoradiotherapy. The acute-phase response was assessed by measurement of C-reactive protein levels. T-cell and monocyte function were assessed by measuring expression of activation markers on these cells in vivo, while neutrophil function was assessed by measurement of intranuclear NF-kappa B in vivo. Intraoperative measurement of splanchnic blood flow was performed by means of gastric tonometry, while pre- and postoperative gut function was estimated by measurement of intestinal permeability.
Keywords: Surgery, M.D.; M.D. Trinity College Dublin